Iranian Mother`s Child Feeding Practices During Diarrhea : A Study in Kerman - Amini-Ranjbar, Seddiqe; Bavafa, Babak (Pakistan Journal of Nutrition, 2007)
Diarrhea as the second common pediatric disease, accounts for approximately 2,000,000 deaths per year in children less than 5 years of age in developing countries. Cultural dictates and nutritional habits in different communities increases the nutritional problems of diarrhoeal episodes. This study was aimed to investigate the practice of Kermani mothers in relation to the nutrition of their children during diarrhea. The present cross-sectional study was performed from March through July 2005 on 330 randomly selected mothers having a 6-24 months child with no underlying disease and at least one acute diarrhea episode during the last two months in her child. Data gathered by using a questionnaire filled out by interviewing subjects. Age and the educational level of subjects in contrast to their job and number of children had no effect on their practice. Most of the subjects (84.2 percent) breastfed their children at the time of healthy state and 80 percent did not give their children rich soup during diarrhea. Most of the subjects quitted giving fats (74.5 percent), Iron supplement (91 percent) and multivitamin (86 percent) at the time of diarrhea but 88 percent continued giving fruit juice. Mothers that their source of knowledge was mass media showed better practice in this regard comparing to others (P< 0.05). Although according to the present study, mothers` practice in Iran is better in comparison to that in other developing countries (India, Pakistan, Nepal,…), we have still serious problems resulting from insufficient training programs and consequently poor knowledge that may lead to persistent improper nutritional habits. Therefore public training especially via mass media is highly recommended to decrease improper nutritional habits during diarrhea.